Variety of Alay Languages on the Market Place for Selling and Buying Online of Ternate - Pipit Aprilia Susanti (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2020)
This brief overview aims to describe the forms of the Alay language especially in the Ternate online market place (a trading forum on the Facebook platform). This type of research is qualitative research, which produces descriptive data in the form of words or words of people and observed behavior. The data collection procedure was carried out by making observations. Meanwhile, the data analysis technique used in this research includes four stages, namely (1) data collection, (2) data reduction, (3) data presentation, and (4) verification / drawing conclusions. The results showed that the use of Alay language in the market place for buying and selling in Ternate was in the form of words by removing certain letters from the words.